Inhibition of Osteoblast Differentiation by JAK2V617F Megakaryocytes Derived From Male Mice With Primary Myelofibrosis - Karagianni, Aikaterini; Matsuura, Shinobu; Gerstenfeld, Louis C.; Ravid, Katya (Frontiers in Oncology, 2022)
Past studies described interactions between normal megakaryocytes, the platelet precursors, and bone cell precursors in the bone marrow. This relationship has also been studied in context of various mutations associated with increased number of megakaryocytes. The current study is the first to examine the effects of megakaryocytes from transgenic mice carrying the most common mutation that causes primary myelofibrosis (PMF) in humans (JAK2V617F) on bone cell differentiation. Organ level assessments of mice using micro-computed tomography showed decreased bone volume in JAK2V617F males, compared to matching controls. Tissue level histology revealed increased deposition of osteoid (bone matrix prior mineralization) in these mutated mice, suggesting an effect on osteoblast differentiation. Mechanistic studies using a megakaryocyte-osteoblast co-culture system, showed that both wild type or JAK2V617F megakaryocytes derived from male mice inhibited osteoblast differentiation, but JAK2V617F cells exerted a more significant inhibitory effect. A mouse mRNA osteogenesis array showed increased expression of Noggin, Chordin, Alpha-2-HS-glycoprotein, Collagen type IV alpha 1 and Collagen type XIV alpha 1 (mostly known to inhibit bone differentiation), and decreased expression of alkaline phosphatase, Vascular cell adhesion molecule 1, Sclerostin, Distal-less homeobox 5 and Collagen type III alpha 1 (associated with osteogenesis) in JAK2V617F megakaryocytes, compared to controls. This suggested that the mutation re-programs megakaryocytes to express a cluster of genes, which together could orchestrate greater suppression of osteogenesis in male mice. These findings provide mechanistic insight into the effect of JAK2V617F mutation on bone, encouraging future examination of patients with this or other PMF-inducing mutations.